A Review On Minimally Invasive Periodontal Surgery In The Treatment Of Infrabony Defects - M. Khairnar, Shreyasi; Rizvi, Alquama; Das, Neelam; Rode, Sadhana; Choure, Govinda; Kamble, Ashlesha (Journal of Neonatal Surgery, 2025)
Minimally invasive periodontal surgery (MIPS) has emerged as a promising approach for treating infrabony defects, offering advantages in clinical outcomes and patient comfort compared to traditional techniques. Therefore in our review we have access them whether they are good for the treatment of infrabony defect with the help of its history, biological aspect, advantage, disadvantage, decision making tree and prevalence